Tick-Host-Pathogen Interactions - Sarah Ir (Frontiers Research Topics, 2018)
Besides causing direct damage associated with blood feeding and in some cases through the excretion of toxins with their saliva, the main relevance of ticks lies in the wide variety of pathogens that they can transmit, including viruses, bacteria, protozoa and helminths. Owing to socioeconomic and environmental changes, tick distribution is changing with incursions of ticks and tick-borne diseases occurring in different regions of the world when the widespread deployment of chemical acaricides and repellents has led to the selection of resistance in multiple populations of ticks. New approaches that are environmentally sustainable and that provide broad protection against current and future tick-borne pathogen (TBP) are thus urgently needed. Such development, however, requires improved understanding of factors resulting in vector competence and tick-host-pathogen interactions. This Research Topic provides an overview of known molecular tick-host-pathogen interactions for a number of TBPs and highlights how this knowledge can contribute to novel control and prevention strategies for tick-borne diseases.